LCMS-based proteomic analysis of susceptible Musa-Meloidogyne incognita interaction and characterisation of partial NBS-LRR resistance gene in Musa acuminata spp. / Mohamad Taufiq Ahmad - Mohamad Taufiq , Ahmad (2017)
Plant-parasitic nematode (PPN) infestation is burdening banana market and economy worldwide. To overcome this problem, an efficient nematode management approach needs to be developed. Since most cultivated bananas are sterile, the chances of obtaining improved traits using conventional breeding programmes are close to none. To complement this limitation, producing transgenic banana lines with an improved trait is seen as an ideal alternative to manage nematode infestation in bananas. Therefore, an overall aim of the studies conducted in this thesis was to obtain an in-depth understanding of the molecular basis of a compatible banana-nematode interaction. Therefore, a proteomics experiment was designed to profile a compatible interaction between Grand naine cultivar (ITC 1256) and Meloidogyne incognita. Two time points were chosen for this experiment namely 30 and 60 days-after-inoculation (dai). A high-throughput Liquid Chromatography Mass Spectrometry (LCMS) Proteomics platform was used to profile banana root proteins involved during the interaction at both time points. A total of 2065 proteins were recovered from this experiment. Statistical analysis carried out on the peptide feature data obtained revealed that 112 proteins recovered at 60-dai time point showed significant abundance changes (ANOVA, p ≤ 0.05) between M. incognita- inoculated and control root tissues. These proteins were divided into ten predicted function groups namely DNA replication, defence, energy-related, catalytic, structural component, carrier, stress response, metabolism, oxidation-reduction and biosynthesis. The proteomics data also revealed that a protein involved in plant defence namely pathogenesis-related protein 1 (ITC1587_Bchr9_P26466) was present at a significantly lower abundance level in M. incognita-inoculated root tissues when compared to control root tissues. However, the involvement of NBS-LRR Resistance (R) gene was not captured by LCMS proteomics platform. Therefore, a molecular-based strategy was adopted to isolate and characterise the gene at both genomic and transcript levels. A pair of degenerate primers was used to target the conserved regions of the R gene. This study had successfully isolated 73 clone sequences. These isolated clones were found to show high sequence similarities with Resistance gene in other Musa spp. with E-values ranging from 0.00 to 2e-14. A phylogenetic Neighbour-Joining tree constructed based on the aligned deduced NBS-LRR Resistance amino acid sequences of eight Musa species together with the isolated cloned sequences revealed that there were six types of NBS-LRR Resistance gene in Musa spp. This study also found that 30% of the isolated cloned sequences to have their open reading frame (ORF) encoding the Resistance protein interrupted. This phenomenon may lead to the occurrence of premature stop codon that led to the formation of pseudogenes.